TEACHER'S EFFORT IN OPTIMIZING THE READING ABILITY OF CLASS I STUDENTS THROUGH ONLINE LEARNING - Cucu Suryana; Naila Kurnia Restu; Dede Margo Irianto; Yeni Yuniarti (PrimaryEdu : Journal of Primary Education, 2022)
This study aims to examine the efforts of teachers in optimizing the reading skill of first grade elementary school students during the pandemic, examine the responses of teachers and parents, and examine the difficulties experienced by teachers and parents in teaching students to read during the pandemic. The research method used is the case study method. The research instruments used were documentation, observation sheets and interviews. The results of this study are the first teacher's efforts in optimizing the reading skill of 1st grade elementary school students during the pandemic is to create a "reading motivation" group with the method of reading a book "read" one day one page that is shared every day in the group. Second, the response of parents is that they feel that the group is a solution to reading problems, motivates students to be more active in learning to read, and it can be facilitates students’ to manage their time. Third, the difficulty experienced by teachers is Hard to communicate with students or hard to motivate students directly, parents who have work activities outside the home so that it is difficult to teach children. The difficulties experienced by parents were obtained using an interview instrument using the google form platform.